The Density of the Urban Fabric and the Population of Residential Areas - Olga S. Glozman; Ivan A. Krasheninnikov (Academia: Архитектура и строительство, 2018)
The modern town planning practice of planning of the urban transport systems development is based on mathematical calculations of traffic flows. When reconstruction or construction of a sufficiently large transport system is planned, specialists apply mathematical modeling of traffic flows. The number of people living or working in a certain area is important source data for modeling traffic flows. In the last decade urban planners faced the problem of determining the population of a quarter or neighborhood. In this article the method of approximate determination of number of inhabitants is based on an analysis of the type of housing. This technique can be used in urban planning in forecasting and modeling of traffic flows. The research "Formation of basic strategic directions for the development of the transport infrastructure of the cities of Russia" was partially supported by the Central Research and Design Institute of the Ministry of Construction and Housing and Communal Services of the Russian Federation (FGBU TsNIIP Minstroy of Russia).